Sociodemographic, Epidemiological and Clinical Profile of the Cases of Hiv/Aids Among Adolescents in Pernambuco State (BRAZIL) - João Victor Batista Cabral; Siglya Soares Ferreira dos Santos; Conceição Maria de Oliveira (Revista Brasileira Multidisciplinar - ReBraM /Brazilian Multidisciplinay Journal, 2015)
Adolescents are a group who has been presenting, in last years, major vulnerability and exposure to risk situations, and HIV infection is an important form of expression of this vulnerability. This is the age group that has the highest incidence of Sexually Transmitted Infections, since more than 25% of new cases of HIV infection occur among young people younger than 25 years. The aim of this study was to describe the sociodemographic, clinical and epidemiological profile of cases of HIV/AIDS among adolescents in the state of Pernambuco (Brazil), occurred between the years 2007-2012. It was conducted an epidemiological study of sectional type with all cases of HIV/AIDS in individuals aged from 13 to 19 years, enrolled in Sinan. Throughout the study period it was found a growth of the Detection Coefficient of cases of HIV/AIDS among adolescents, ranging from 0.87 (2007) to 3.59 (2012) per 100,000 inhabitants, an increase of 312.64%. These cases were characterized mostly by female (56.59%) aged 18 to 19 years (67.45%), mulatto and black color (58.91%), resident in urban area (95.35%), concentrated according to residence, notification and treatment cities in Recife and Jaboatão dos Guararapes, infected through sexual intercourse (74.42%), considering among men (40.63%) through homosexual relations and among women (93.75%) through heterosexual intercourse. Most cases were defined by CDC criteria Modified (93,80%) and (12.40%) died due to AIDS.